LANGUAGE LEARNING IN THE EIGHTIES: THE CURRENT STATE OF EDUCATION IN AMERICA - Moffett, James (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
No one is better entitled to indulge in speculation about the future of English studies than James Moffett. Ten years ago, his work of theory and rationale, "Teaching the Universe of Discourse," lifted the teaching of English fifty years forward into the Seventies. It provided, it seemed for the first time, an intellectually satisfying analysis of great range, depth, and sensitivity for the distinctive processes of learning the language by which we think, and it remains a model of rational pedagogy in the field. Here he reviews the recent difficulties of this most public of school subjects, and then proceeds to raise our sights (and doubtless some eyebrows) with a forward look that takes into serious account many signs that are so much with us as to be subiect to our too light dismissal. Here is one driver not obsessed by what is to be seen only in the rear-view mirror.